Effect of Caffeine on Hemodynamics and Autonomics Parameters in Hypertensive Women after Aerobic Exercise - Nobrega, Tereza Karoline Sarmento da (2017)
The aim of this study was to analyse the effect of caffeine consumption on cardiac autonomic modulation and arterial blood pressure after aerobic exercise in hypertensive women. Twelve hypertensive women participated in this study (55±4 years old), habitual consumers of caffeine. The electrocardiogram and the arterial blood pressure were recorded during rest and after aerobic exercise. All subject ingested caffeine or placebo (4mg/kg), waited 30 minutes and exercised on a treadmill for 30 minutes with intensity of 60% and 70% of the reserve heart rate. Systolic arterial blood pressure rose significantly in the caffeine session compared to rest and placebo session (p < 0.05). Spectral component of low frequency and sympathovagal balance increased dramatically when compared to baseline in caffeine session. In contrast, during the placebo session, the low frequency and sympathovagal balance decreased significantly (p < 0.05). When compared the caffeine and placebo sessions, it could be seen that the low frequency and sympathovagal balance were significantly higher in caffeine session (p < 0.05). Thus, it can be suggested that the consumption of caffeine increased the cardiac sympathetic activity with resulting increase of systolic arterial blood pressure after aerobic exercise, which could be related to a possible hypertensive reaction in hypertensive middle-aged women.